Gender, Political Resources, and Expressions of Democratic Evaluations - Hansen Michael A; Goenaga Agustin (Taylor and Francis Group, 2025)
Are certain citizens more likely to feel entitled to evaluate the quality of democratic institutions in their country? Previous studies show that women are more likely than men to answer "don't know" when asked to express their views about the state of democracy. This article analyzes how political knowledge and internal efficacy contribute to such a gender gap in item non-response rates in research on democratic evaluations. Based on an original survey in the United States (N = 1,093), we do not find that respondents' political knowledge is associated with a higher probability of expressing their views about democracy. However, we do find that this is the case for internal efficacy and that these effects are largely driven by women. These findings suggest that gendered social roles about who is entitled or expected to express their views about democracy lie behind the gender gap in item non-response rates.